Synthesis, structure, and unprecedented solubility of lipophilic borate salts - Wrede, Michael; Frank, Viktoria; Kannenberg, Gerri; Rominger, Frank; Straub, Bernd Franz (Inorganica chimica acta, 2011)
The multi-gram scale preparation of halide free lipophilic borate salts from inexpensive precursor compounds 3,3′,5,5′-tetra-tert-butyl-2,2′-biphenol and tetrahydridoboranate salts is reported. The so-called “bortebate” anion is more stable against water and bases than its aluminum analog “altebate”, but bortebate formation is significantly slower. Bortebate salts are highly soluble in hydrocarbon solvents, e.g. >35mmol/L lithium bortebate in pentane at 20°C. Quantitative salt metathesis reactions between sodium bortebate and halide salts can be easily achieved by precipitation of the sodium halide in methylene chloride.